Relationship Between Family History of Stroke, Hypertension and Smoking History with The Incidence of Ischemic Stroke in Stroke Patients - Timur, Insan Rabbani; Tunjung, I Wayan; Iing, Iing; Setiarini, Rohmania (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The most prevalent kind of stroke and a major global cause of disability and death is ischemic stroke. According to data, smoking and hypertension are the main risk factors for stroke, which is very common in Indonesia, especially in Central Lombok. Numerous studies also link the likelihood of specific stroke subtypes to family history. Based on these facts, the purpose of this study is to determine and examine the association between the incidence of ischemic stroke in stroke patients at Praya Regional General Hospital, Central Lombok, and smoking, hypertension, and family history of stroke. This study employs an observational analytic approach with a cross-sectional research design. The sampling technique used is purposive sampling. Data were analysed using the Chi-Square test with a significance level of p < 0.05 and multiple logistic regression analysis. Of the 108 respondents, univariate analysis showed that 28.7% had a family history of stroke, 74.1% had hypertension, and 50.9% had a history of smoking. Bivariate analysis revealed no significant association between family history of stroke and ischemic stroke (p = 0.301). In contrast, hypertension (p = 0.007) and smoking history (p = 0.016) demonstrated significant associations. Multivariate analysis indicated that hypertension increased the likelihood of ischemic stroke by four times (Exp(B) = 4.074; p = 0.004), while smoking history elevated the risk by 3.3 times (Exp(B) = 3.364; p = 0.009). The conclusion is that hypertension and smoking history have a significant relationship with ischemic stroke, increasing the risk by 3.9 times and 3.2 times respectively, while family history of stroke does not show a significant relationship.